Pemanfaatan Rempah Tradisional dalam Peningkatan Mutu dan Daya Simpan Geplak Sirsak (Annona muricata) - Amila Firdhauzi; Wikiyas L Saputri; Nanik Suhartatik; Akhmad Mustofa (AGRITEKNO: Jurnal Teknologi Pertanian, 2025)
Geplak is a traditional food from Bantul Regency, Yogyakarta, made from grated coconut and sugar, which is roasted and shaped into small, colorful balls. The increasing consumer demand for natural traditional foods has encouraged the development of geplak with addition of soursop (Annona muricata) and traditional spices, resulting in a functional product with enhanced shelf life. This study aimed to evaluate the effect of adding traditional spices (cinnamon, clove, and nutmeg) on the physicochemical properties and shelf life of soursop geplak during storage. The geplak was prepared from a mixture of coconut, young papaya, and soursop, with each spice added at 0.4% (w/w). The samples were stored at room temperature and analyzed on days 0, 5, 10, and 15. The parameters analyzed included color (Chroma), texture (crispness and hardness), pH, moisture content, water activity (aw), and antioxidant activity (DPPH method). The results showed that cinnamon produced the highest color intensity (22.05) and exhibited the highest antioxidant activity, with only a slight decrease from 82.41% to 79.31% during storage. Nutmeg resulted in the highest hardness (445.51 N) and crispness (3431.9 Nmm) on day 0. The pH increased during storage, with cinnamon reaching 5.52 on day 15. Although moisture content increased significantly, it remained within the acceptable range of the geplak quality standard, while water activity remained relatively stable with an average value of 0.65. The addition of spices, particularly cinnamon, effectively maintained the quality of soursop geplak and extended its shelf life without the use of synthetic additives, in accordance with SNI 01-4298-1996. These findings highlight the potential of soursop geplak as an innovative local functional food.